2020
DOI: 10.3389/fonc.2020.00873
|View full text |Cite
|
Sign up to set email alerts
|

Identification of an Autophagy-Related Prognostic Signature for Clear Cell Renal Cell Carcinoma

Abstract: Abnormal autophagy is closely related to the development of cancer. Many studies have demonstrated that autophagy plays an important role in biological function in clear cell renal cell carcinoma (ccRCC). This study aimed to construct a prognostic signature for ccRCC based on autophagy-related genes (ARGs) to predict the prognosis of ccRCC. Differentially expressed ARGs were obtained from ccRCC RNA-seq data in The Cancer Genome Atlas (TCGA) database. ARGs were enriched by gene ontology (GO) and Kyoto Encyclope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 40 publications
0
22
0
Order By: Relevance
“…Survival analysis and Cox regression analysis indicated that expression of IGFLR1 was a prognostic factor in ccRCC patients, rather than an independent prognostic factor (Sichani et al, 2010). Besides, although a number of previous studies have constructed prognostic risk models based on clinical factors, gene signature, or taking both into account (Chang et al, 2018;Chen et al, 2019Chen et al, , 2020Xu D. et al, 2020;Xu W.H. et al, 2020), IGFLR1 has not been reported as a factor in model construction.…”
Section: Discussionmentioning
confidence: 99%
“…Survival analysis and Cox regression analysis indicated that expression of IGFLR1 was a prognostic factor in ccRCC patients, rather than an independent prognostic factor (Sichani et al, 2010). Besides, although a number of previous studies have constructed prognostic risk models based on clinical factors, gene signature, or taking both into account (Chang et al, 2018;Chen et al, 2019Chen et al, , 2020Xu D. et al, 2020;Xu W.H. et al, 2020), IGFLR1 has not been reported as a factor in model construction.…”
Section: Discussionmentioning
confidence: 99%
“…A study conducted by Ding et al on invasive liver cancer yielded similar ndings [32]. Bioinformatics analysis performed by Chen et al revealed that the biological processes of the clear cell renal cell carcinoma (ccRCC) low-risk group was related to the regulation of autophagy [33]. Li et al also found that the positive regulation of autophagy and enrichment of immune activation pathways were more associated with patients in the low-risk group than those in the high-risk group [14].…”
Section: Discussionmentioning
confidence: 89%
“…Dunkle et al found that the rate of apoptosis of peripheral T cells with CFLAR de ciency increased [42]. Following bioinformatics analysis of ARGs in ccRCC, Chen et al found that PRKCQ was associated with poor OS in patients with ccRCC, and may be used to evaluate their prognosis [33]. In summary, these genes are often associated with immune response and autophagy in tumors.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies indicated that AGRs-based signature can serve as effective biomarkers for predicting patient's prognosis [22][23][24][25], but the role in sarcoma patients remains unclear. In the present study, two ARGs-based signatures were generated to predict the OS and DFS for sarcoma patients, respectively.…”
Section: Construction Of Arg Signatures For Os and Dfs Of Sarcoma Patmentioning
confidence: 99%